Molecular Approaches to the Treatment, Prophylaxis, and Diagnosis of Alzheimer's Disease: Novel PET/SPECT Imaging Probes for Diagnosis of Alzheimer's Disease - Masahiro Ono; Hideo Saji (Elsevier, 2012)
Alzheimer's disease (AD) is a neurodegenerative disease of the brain associated with irreversible cognitive decline, memory impairment, and behavioral changes. Postmortem brains of AD patients reveal neuropathologic features, in particular the presence of senile plaques (SPs) and neurofibrillary tangles (NFTs), which contain β-amyloid peptides and highly phosphorylated tau proteins. Currently, AD can only be definitively confirmed by postmortem histopathologic examination of SPs and NFTs in the brain. Therefore, SPs and NFTs in the brain may be useful as biomarkers for the differential diagnosis of AD; the detection of individual SPs and NFTs in vivo by positron-emission tomography (PET) or single-photon emission computed tomography (SPECT) should improve diagnosis and also accelerate discovery of effective therapeutic agents for AD. Many PET/SPECT imaging probes for SPs have already been developed. Several of the PET probes have been shown in clinical trials to be useful for the imaging of β-amyloid plaques in living brain tissue. More recently, the development of PET/SPECT probes for in vivo imaging of NFTs is an active area of study in the field of molecular imaging because the appearance of NFT pathology correlates well with clinical severity of dementia. We will review current research on the development of PET/SPECT imaging probes for in vivo detection of SPs and NFTs and their application to diagnosis and therapy of AD. Keywords:: Alzheimer's disease, senile plaque, neurofibrillary tangle, positron-emission tomography (PET), single-photon emission computed tomography (SPECT)